Adsorption, Kinetic and Thermodynamic Studies for the Adsorption of Cadmium onto Combination of Chitosan and Coffee Ground Activated Carbon - Nurhidayanti, Nisa; Riyadi, Agus (Rekayasa, 2024)
The presence of cadmium in water due to its natural mobility can cause the nature of the water to become toxic and threaten the surrounding ecosystem when it accumulates in the food chain. The aim of this study was to investigate the maximum adsorption capacity using an isothermal model, to determine the rate of adsorption kinetics using chitosan and coffee powder adsorbents in reducing cadmium concentrations in industrial wastewater, and to investigate its thermodynamic magnitude. The research method was applied with laboratory experiments followed by quantitative data analysis to determine the isothermal model and adsorption kinetics. The results showed that the adsorption isotherm follows the Langmuir isotherm model with a correlation coefficient of 0.9970 and a maximum adsorption capacity of 0.7546 mg.g-1, which indicates that the chemical adsorption occurs in a monolayer, where the  adsorption sites are homogeneously distributed with the adsorption energy. Permanent and negligible interactions between cadmium molecules (adsorbate) and adsorbent. Thus the pseudo second order kinetic model is a better way to explain the reaction rate for cadmium in combination chitosan and coffee ground activated carbon. Negative ΔGo values indicate that the adsorption reaction takes place spontaneously, ΔHo of 0.3467 indicates an endothermic reaction, and ΔSo of 3.5296 indicates an increase in the randomness of the adsorption process at the adsorbent interface and cadmium during adsorption.